Advances in oxidative stress in pathogenesis of diabetic kidney disease and efficacy of TCM intervention - Xiaoju Ma; Jingru Ma; Tian Leng; Zhongzhu Yuan; Tingting Hu; Qiuyan Liu; Tao Shen (Renal Failure, 2023)
Diabetic kidney disease (DKD) is a common complication of diabetes and has become the leading cause of end-stage kidney disease. The pathogenesis of DKD is complicated, and oxidative stress is considered as a core of DKD onset. High glucose can lead to increased production of reactive oxygen species (ROS) via the polyol, PKC, AGE/RAGE and hexosamine pathways, resulting in enhanced oxidative stress response. In this way, pathways such as PI3K/Akt, TGF-β1/p38-MAPK and NF-κB are activated, inducing endothelial cell apoptosis, inflammation, autophagy and fibrosis that cause histologic and functional abnormalities of the kidney and finally result in kidney injury. Presently, the treatment for DKD remains an unresolved issue. Traditional Chinese medicine (TCM) has unique advantages for DKD prevention and treatment attributed to its multi-target, multi-component, and multi-pathway characteristics. Numerous studies have proved that Chinese herbs (e.g., Golden Thread, Kudzuvine Root, Tripterygium glycosides, and Ginseng) and patent medicines (e.g., Shenshuaining Tablet, Compound Rhizoma Coptidis Capsule, and Zishen Tongluo Granule) are effective for DKD treatment. The present review described the role of oxidative stress in DKD pathogenesis and the effect of TCM intervention for DKD prevention and treatment, in an attempt to provide evidence for clinical practice.